P3 Ustekinumab for the treatment of moderate to severe ulcerative colitis: a multicentre UK cohort study. (19th June 2022) - Al-Hillawi, Lulia; Honap, Sailish; Baillie, Samantha; Bancil, Aaron; Kok, Klaartje; Patel, Kamal; Walsh, Alissa; Irving, Peter; Samaan, Mark
Abstract : Introduction: Ustekinumab is an IL-12/23 receptor antagonist licensed for the treatment of ulcerative colitis (UC). Clinical trial data were promising however real-world data are limited. The aim was to assess the safety and effectiveness of ustekinumab in UC in a real-world setting Methods: This was a multicenter, retrospective, observational cohort study across four tertiary IBD referral units in the UK between February 2020 and January 2022. Disease activity was assessed using the Simple Clinical Colitis Activity Index (SCCAI). Clinical remission was defined as a SCCAI ≤2. The primary endpoints were rates of corticosteroid-free clinical remission (CSFR) at week 16 and at week 26. Objective disease assessment outcomes, including fecal calprotectin (FCAL), were also collected. Results: 110 patients with UC [65% male; median age 40 (interquartile (IQR) range 29-59); 96% with prior biologic and/or tofacitinib exposure] with a median follow up duration of 28 weeks (IQR 17-47). CSFR was 36% (18/50) at week 16 and 33% (13/39) at week 26, corresponding with a significant fall in SCCAI from 6 (IQR 4-8) at baseline to 3 (IQR 0-5) at week 26, p<0.001. By week 16, there was improvement of median FCAL measurements, which fell from a baseline of 610mcg/g [IQR 333-1100] to 102mcg/g [IQR 54-674] at week 16. In multivariate analyses, only current smokers were associated with ustekinumab discontinuation. At the end of follow up, 15% (17/110) had discontinued treatment; 4 patients due to primary non-response, 9 due to loss of response, and 1 patient discontinued for family planning. Treatment was discontinued in only 3 patients due to adverse events. Conclusions: In the largest real-world study to date, ustekinumab was shown to be effective with a reassuring safety profile in a refractory cohort of patients.